Performance and forage intake of range cows as affected by mineral supplement and delaying winter supplemental feed - Pruitt, R.J.; Peischel, H.A.; Smith, E.F.; Schalles, R.R.; Owensby, Clenton E. (Kansas State University. Agricultural Experiment Station, 2011)
Polled Hereford cows on native Flint Hills pasture not supplemented until February lost more weight from November to February and were in poorer condition during the winter and early spring than cows supplemented beginning in November. But birth weights, weaning weights, conception percentages, and calving intervals were similar for both groups. Balancing for phosphorus, potassium, and copper deficiencies in the forage did not improve cow or calf performance. Forage intake ranged from 1.70% of fall body weight when dormant winter grass was low in protein and digestibility to 3.45% when spring grass was higher in protein and more digestible. Forage intake was not influenced by winter supplement program but was slightly higher when minerals were fed. Although forage consumption increased with cow size, it was not affected by level of milk production.
Keywords: Beef; Performance; Forage intake; Winter